An Examination of the Antecedents of Subjective Career Success among a Managerial Sample in Singapore - ARYEE, Samuel (Institutional Knowledge at Singapore Management University, 1994)
Antecedents of subjective career success are examined using data obtained with a questionnaire instrument from managerial employees in Singapore. The choice of antecedents was informed by recent calls to place research on career issues in the context of an individual's life roles. Confirmatory factor analysis (LISREL VII) was used to examine the one-factor and three-factor models hypothesized to underlie the subjective career success data. The results revealed a 3-factor model to have adequate fit statistics - financial and hierarchical success, and career satisfaction. The antecedent sets of human capital, work values, family and structural or work variables accounted for over 40% of the explained variance in each career success dimension. While the career success dimensions were influenced by different variables, individual-organizational value congruity, quality of parental role and internal labor market emerged as consistent antecedents of the career success dimensions.